Characteristics and Echogenicity of Clinical Ultrasound Contrast Agents: An In Vitro and In Vivo Comparison Study. (27th February 2017) - Hyvelin, Jean‐Marc; Gaud, Emmanuel; Costa, Maria; Helbert, Alexandre; Bussat, Philippe; Bettinger, Thierry; Frinking, Peter
Abstract : Objectives: To compare physicochemical characteristics and in vitro and in vivo contrast‐enhanced ultrasound imaging performance of 3 commercially available ultrasound contrast agents: SonoVue (Bracco Imaging SpA, Colleretto Giacosa, Italy; also marketed as Lumason in the USA), Definity (Lantheus Medical Imaging, North Billerica, MA) and Optison (GE Healthcare AS, Oslo, Norway). Methods: Physicochemical characteristics were measured with a Multisizer Coulter Counter (Beckman Coulter, Fullerton, CA). Two ultrasound systems (Aplio 500; Toshiba Medical Systems Corp, Tochigi‐ken, Japan; and Logiq E9; GE Healthcare, Little Chalfont, England) were used with different transducers. Contrast enhancement was measured in vitro by dose‐ranging measurements using a custom‐built beaker setup; in vivo imaging performances were compared in pigs (heart and liver) and rabbits (liver). Quantitative analyses were performed with VueBox quantification software (Bracco Suisse SA, Plan‐les‐Ouates, Switzerland). Results: Measured physicochemical characteristics were in agreement with those provided by the manufacturers. In vitro data demonstrated that the performance of SonoVue was similar to or better than that of Definity but superior to Optison (normalized scattered power 2‐ to 10‐fold higher with SonoVue). Similar results were obtained in vivo, although the duration of enhancement in the pig heart was longer for SonoVue compared to Definity, and quantitative analysis revealed higher enhancement for SonoVue (1.5‐fold increase). For liver imaging, SonoVue and Definity showed similar contrast enhancement and duration of enhancement, but compared to Optison, both peak enhancement and duration of enhancement were superior for SonoVue (up to 2‐fold increase). Conclusions: Imaging performance of SonoVue was similar to or slightly better than that of Definity, but it was superior to Optison for the conditions used in this study.